2006
DOI: 10.1002/ceat.200500222
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Kinetics and Morphology of Gas Hydrate Formation

Abstract: The kinetics and morphology of ethane hydrate formation were studied in a batch type reactor at a temperature of ca. 270-280 K, over a pressure range of 8.83-16.67 bar. The results of the experiments revealed that the formation kinetics were dependant on pressure, temperature, degree of supercooling, and stirring rate. Regardless of the saturation state, the primary nucleation always took place in the bulk of the water and the phase transition was always initiated at the surface of the vortex (gas-water interf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…For carbon dioxide, nucleation at the gas-liquid interface started on the wall and the hydrate layer grew into the liquid bulk, which was confirmed by Takeya et al (2000) with a highspeed video camera. Additional data for nucleation in the interfacial region for quiescent systems are found in the literature for ethane (Hussain et al, 2006), propane (Gayet et al, 2005), dichlorofluoroethane (Li et al, 2005) and methane-propane hydrates, all formed from distilled water. Working with diluted SDS solutions, Lin et al (2004) and Gayet et al (2005) observed nucleation at the reactor wall, close to the gas-liquid interface, for pure methane and propane hydrates, respectively, with a rapid growth along the wall in the gas side.…”
Section: Experimental Studies On Hydrate Nucleationmentioning
confidence: 95%
“…For carbon dioxide, nucleation at the gas-liquid interface started on the wall and the hydrate layer grew into the liquid bulk, which was confirmed by Takeya et al (2000) with a highspeed video camera. Additional data for nucleation in the interfacial region for quiescent systems are found in the literature for ethane (Hussain et al, 2006), propane (Gayet et al, 2005), dichlorofluoroethane (Li et al, 2005) and methane-propane hydrates, all formed from distilled water. Working with diluted SDS solutions, Lin et al (2004) and Gayet et al (2005) observed nucleation at the reactor wall, close to the gas-liquid interface, for pure methane and propane hydrates, respectively, with a rapid growth along the wall in the gas side.…”
Section: Experimental Studies On Hydrate Nucleationmentioning
confidence: 95%
“…Similar to ice formation and melting, gas hydrate may undergo phase transitions of three stages, i.e., nucleation, , growth, , and dissociation. , Accumulated research efforts via experimental studies , and modeling/simulation work , have been made in attempt to gain more understanding of hydrate formation and dissociation phenomena for decades. It is relatively easy to monitor and study hydrate growth and dissociation on a macroscopic scale. ,, During nucleation, the water–gas clustering process is an energy battle between the volume excess free energy (favorable, reduced enthalpy) and surface excess free energy (unfavorable, reduced entropy) in the metastable region. Nucleation is stochastic and intractable because initial embryos of hydrate clusters of different sizes would not obtain the critical size to form stable nuclei until the free energy barrier of pushing away the old phases is overcome. , Only a nucleus surpassing such energy barrier would reach critical size for sustainable nucleation and trigger macroscopic growth.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies on the phase equilibrium and kinetics of gas hydrate formation and dissociation have been reported by many researchers, but most of them are on hydrate formation/dissociation in pure or binary gas mixture [3][4][5][6][7][8][9] . On the other hand, there are very limited experimental data of hydrate formation and dissociation conditions in ternary gas mixtures [10][11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…The objective of this study is to see the effect of promoter for storing natural gas as hydrates. In this study, effect of sodium dodecyl sulfate (SDS) and tetrahydrofuran (THF) on phase equilibrium condition and formation kinetics of CH 4…”
Section: Introductionmentioning
confidence: 99%